Trapeziectomy with Ligament Reconstruction and Tendon Interposition versus Trapeziometacarpal Joint Replacement for Thumb Carpometacarpal Osteoarthritis: A Systematic Review and Meta-Analysis - Qureshi, Mobeen Khalid; Halim, Usman Ali; Khaled, Ahmad Sulaiman; Roche, Simon John; Arshad, Mohammed Shoaib (Journal of Wrist Surgery, 2021)
Background The trapeziometacarpal articulation in the thumb is a joint that is second-most commonly affected by osteoarthritis, and this can lead to considerable hand pain and disability. Currently, there is a multiplicity of surgical options available to address this problem, yet none has proven to be significantly superior to the others.Objective This study aims to compare the outcome of trapeziectomy with ligament reconstruction and tendon interposition versus trapeziometacarpal joint replacement for thumb carpometacarpal osteoarthritis.Materials and Methods A systematic review and meta-analysis was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement standards. The NICE Healthcare Databases Advanced Search (HDAS) tool was used to search articles. One randomized controlled trial (RCT), one prospective cohort study and two retrospective cohort studies were identified.Results Our results demonstrate a significant difference in the Quick Disabilities of the Arm Shoulder and Hand (QDASH) score between the trapeziectomy with ligament reconstruction and tendon interposition (LRTI) and Joint Replacement groups with the joint replacement group exhibiting better QDASH scores than the LRTI group. We also found that those who had a joint replacement had a significantly better thumb opposition than those in the LRTI group, as demonstrated by a superior Kapandji score. However, the complication rate of joint replacement appears to be higher.Conclusion Our study reveals that while both treatment options are valid, the limited body of evidence currently available shows that joint replacement carries more risks and thus should not replace the current standard treatment of trapeziectomy with LRTI. This study highlights the need for more trials to be performed to more accurately compare the two treatment modalities. For the time being, we advocate that joint replacement is only performed by surgeons who perform this procedure regularly to reduce the risk of complications.
Keywords: trapeziectomy; carpometacarpal osteoarthritis; carpometacarpal joint; ligament reconstruction and tendon interposition